Rancang Bangun Sistem Informasi dan Monitoring Database di Lembaga Layanan Disabilitas Universitas Pamulang - Julyansyah, Iqbal; Ilham, Farizi; Widayanti, Atika; Sayida Bilqis, Salsa (Jurnal Pustaka Data (Pusat Akses Kajian Database, Analisa Teknologi, dan Arsitektur Komputer), 2026)
Data management for students with disabilities at the Disability Service Unit (LLD) of Pamulang University was still conducted manually using paper forms and spreadsheets, leading to recording errors, reporting delays, and outdated academic information. This study aims to design and develop a web-based monitoring information system using the Laravel framework, MySQL database, and Agile Development method. The system includes student data management, Excel-to-MySQL conversion using Laravel Excel, and academic progress monitoring through IPS and GPA visualization using Chart.js. Black Box Testing results showed that all system features, including login, student data management, Excel import, data validation, and academic monitoring, functioned successfully according to user requirements with a 100% testing success rate. The system was also able to accelerate disability student data management through automatic Excel-to-MySQL conversion and provide real-time academic monitoring through IPS and GPA graphical visualization. Furthermore, the system provides multi-level access for Admin, Head of Division, and Staff within an integrated platform, thereby improving data management efficiency and academic monitoring accuracy for students with disabilities at Pamulang University.